Accommodating the discarnate: Thai spirit houses and the phenomenology of place - Pearce, Michael (Material religion, 2011)
In Thailand, many homes possess small shrines for locality and guardian spirits. In Thai the shrines are known by various names denoting the ethereal occupants and their various spheres of influence. In English they are referred to collectively as "spirit houses." By exploring the ways in which these shrines are used by Thai people through two case studies, this article addresses the prevalence of spirit houses in contemporary urban locations, an area which scholarship on Thai popular religion has largely neglected. Based upon eighteen months of fieldwork in three Thai cities, the article argues that the ornate shrines which adorn many house compounds in contemporary urban Thailand tie into local understandings of the social character of places. It is suggested that the persistence of spirit houses can be partly understood through their roles as mediators of the phenomenological experience of certain places. Spirit houses are one part of a gathering process that imbues places with significant meaning. The shrines exemplify that culturally specific interactions and engagements with spirits associated with certain places influence how the phenomenological qualities of these places are constructed and experienced.